Are reading difficulties associated with bullying involvement?. (December 2017) - Turunen, Tiina; Poskiparta, Elisa; Salmivalli, Christina
Abstract: Reading difficulties (RDs) are easily noticed by classmates, may cause frustration in the affected students, and are often accompanied by emotional, behavioral, and interpersonal problems at school. Although interviews with students with RDs have revealed bullying experiences, whether RDs actually increase the risk of bullying involvement has not been investigated before. We tested the association of self-reported RDs with peer-reported involvement in bullying in a nationally representative sample of 17, 188 students (grades 3–8) from 1045 classrooms in 147 schools. Results indicated that experienced difficulties in the most fundamental learning skill seem to put students at risk especially for victimization at school (viewed by peers as victims and bully/victims), when gender, level of schooling, self-esteem, and difficulties in math were taken into account. In general, over a third of students with RDs were involved in bullying as victims, bullies, or bully/victims, compared with approximately a fifth of students without RDs. Highlights: Students reporting reading difficulty are involved in bullying more often than others. One third of students reporting RDs are victims, bullies, or bully-victims according to their peers. Reading difficulties increase victimization risk beyond math and self-esteem problems.